2019
DOI: 10.3390/ijerph17010236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Activity-Based Working and Height-Adjustable Desks on Physical Activity, Sedentary Behavior, and Space Utilization among Office Workers: A Natural Experiment

Abstract: It has been reported that office environment is an important determinant of physical activity (PA) and sedentary behavior (SB) in office workers. However, the effect of changes in office environment (office renovation) is unclear. The purpose of this study was to examine PA, SB, and space utilization changes among office workers in response to office renovation. This study was a natural experiment at three offices of a single company in Tokyo, Japan. The participants were, 13 workers from one office in the ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The use of active workstations is a powerful intervention 33 ; hence, the use of height‐adjustable desks (sit‐stand workstations) would be a useful interventional strategy for telecommuting workers to reduce SB and interrupt prolonged SB bouts, not only at their offices but also at home. In addition, a natural experimental study showed that office renovation by the introduction of activity‐based working and installation of height‐adjustable desks has a favorable effect on increasing PA as well as decreasing SB 34 . In addition to the above environmental interventions, other interventions for SB at the individual, social, and organizational levels have been suggested from the viewpoint of the ecological model 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of active workstations is a powerful intervention 33 ; hence, the use of height‐adjustable desks (sit‐stand workstations) would be a useful interventional strategy for telecommuting workers to reduce SB and interrupt prolonged SB bouts, not only at their offices but also at home. In addition, a natural experimental study showed that office renovation by the introduction of activity‐based working and installation of height‐adjustable desks has a favorable effect on increasing PA as well as decreasing SB 34 . In addition to the above environmental interventions, other interventions for SB at the individual, social, and organizational levels have been suggested from the viewpoint of the ecological model 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Movement-based breaks increase the workers' perception of their wellbeing as long as they do not significantly cut into productive work time (Haapakangas et al, 2018 ). Exercise during the usual daily workflow makes the worksite more proactive, which enhances workers' self-awareness and physical efficiency (Tsai and Wang, 2016 ; Jindo et al, 2019 ). Again, the companies benefit more from promoting employees' physical activity: productivity, work performance, and workers' mood all improve (Grimani et al, 2019 ), and medical costs and costs from absenteeism become considerably lower (Baicker et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of PA was presented in the 26 studies (Schultz et al 2017;Dill et al 2014;Auchincloss et al 2019;McCormack et al 2016;Ogilvie et al 2016;Simões et al 2017;Lee et al 2017;Cohen et al 2012Cohen et al , 2019Jindo et al 2020;Cranney et al 2016;Brittin et al 2017;Andersen et al 2017;Zhu et al 2018;Sun et al 2020;Mölenberg et al 2019a;Fitzhugh et al 2010;Veitch et al 2012;Aittasalo et al 2019;Hooper et al 2018;Quigg et al 2012;Giles-Corti et al 2013;McGavock et al 2019;Demant Klinker et al 2015;Ward Thompson et al 2013;Jancey et al 2016) shown in Table 3 in which the effectiveness of the programs was variable. The level of PA was greater in some structural-level environmental modifications than in others while no difference between intervention and control groups were observed.…”
Section: Effectiveness Of the Structural Modificationsmentioning
confidence: 99%
“…Seventeen studies (Schultz et al 2017;Dill et al 2014;McCormack et al 2016;Ogilvie et al 2016;Simões et al 2017;Cohen et al 2012;Jindo et al 2020;Brittin et al 2017;Andersen et al 2017;Mölenberg et al 2019a;Veitch et al 2012;Aittasalo et al 2019;Hooper et al 2018;McGavock et al 2019;Demant Klinker et al 2015;Ward Thompson et al 2013;Jancey et al 2016) reported an increase in the PA level post-structural modification. For example, an increase in total activity time, varying between 10 and 30 min, a 6-28% increase and an increase of between 38 and 369 users participating in the activity were found between the pre-and post-structural modifications.…”
Section: Activity Levelmentioning
confidence: 99%
See 1 more Smart Citation